2017
DOI: 10.1093/sleep/zsx087
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sleep Duration During Transition to Statutory Retirement: A Longitudinal Cohort Study

Abstract: Study Objectives: This study examined whether sleep duration changes during the transition from full-time work to statutory retirement and, if this were the case, which pre-retirement factors, including sociodemographic, work, lifestyle and health factors, predict these changes. [CI] 6 h 54 min to 7 h 6 min) to 7 hours and 22 minutes (95% CI 7 h 16 min to 7 h 27 min); thus, mean increase being 22 minutes. Increase in sleep duration was greatest in those who were short sleepers, heavy drinkers or had sleep diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 33 publications
7
41
2
Order By: Relevance
“…However, findings from SHHS showed that TST decreased at older age, but sleep latency increased, an effect similar to our findings . Transition to retirement leads to an increase in sleep duration . Increased TST and a positive association with long sleep duration were found in our retired participants.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, findings from SHHS showed that TST decreased at older age, but sleep latency increased, an effect similar to our findings . Transition to retirement leads to an increase in sleep duration . Increased TST and a positive association with long sleep duration were found in our retired participants.…”
Section: Discussionsupporting
confidence: 89%
“…3 Transition to retirement leads to an increase in sleep duration. 48 Increased TST and a positive association with long sleep duration were found in our retired participants. A study of older adults in China showed an increased risk of short and long sleep duration in unmarried participants.…”
Section: Discussionmentioning
confidence: 50%
“…Retirement from work has recently been reported to be associated with sleeping more [1,2], as well as experiencing fewer sleep difficulties [3][4][5], and less mental and physical fatigue [6] after retirement. These favorable changes in sleep have been hypothesized to partly result from the removal of work-related stressors after retirement [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous research has shown that retirement is associated with increased leisure physical activity9 and sleep duration10 most likely due to increased time availability, restructure of leisure activities and awareness of one’s own health and well-being 11 12. However, retirement has also been listed as a strong determinant for engaging sedentary behaviour 13.…”
Section: Introductionmentioning
confidence: 99%